Nitrate reductase is required for sclerotial development and virulence of Sclerotinia sclerotiorum - Wei, Junjun; Yao, Chuanchun; Zhu, Zonghe; Gao, Zhimou; Yang, Guogen; Pan, Yuemin (Frontiers in Plant Science, 2023)
Sclerotinia sclerotiorum, the causal agent of Sclerotinia stem rot (SSR) on more than 450 plant species, is a notorious fungal pathogen. Nitrate reductase (NR) is required for nitrate assimilation that mediates the reduction of nitrate to nitrite and is the major enzymatic source for NO production in fungi. To explore the possible effects of nitrate reductase SsNR on the development, stress response, and virulence of S. sclerotiorum, RNA interference (RNAi) of SsNR was performed. The results showed that SsNR-silenced mutants showed abnormity in mycelia growth, sclerotia formation, infection cushion formation, reduced virulence on rapeseed and soybean with decreased oxalic acid production. Furthermore SsNR-silenced mutants are more sensitive to abiotic stresses such as Congo Red, SDS, H2O2, and NaCl. Importantly, the expression levels of pathogenicity-related genes SsGgt1, SsSac1, and SsSmk3 are down-regulated in SsNR-silenced mutants, while SsCyp is up-regulated. In summary, phenotypic changes in the gene silenced mutants indicate that SsNR plays important roles in the mycelia growth, sclerotia development, stress response and fungal virulence of S. sclerotiorum.